Metamorfose Nisan Aceh, Dari Masa Ke Masa - Repelita Wahyu Oetomo (Berkala Arkeologi Sangkhakala, 2016)
AbstractTombstones in Aceh have gone through changes of shapes (metamorphosis) from simple shapes to the shapes like we know today. The metamorphosis began with some simple tombstones like the ones at Samudera Pasai, the starting point of Islam dispersal in the archipelago. Until now Samudera Pasai is believed to be the first Islamic kingdom in the archipelago, which made it a place to adopt the shapes of tombstones from the earlier period, which is the Hindu-Buddhist period. Other places that are thought to be the earliest Islam areas in the archipelago include among others Lamreh/Lamuri in Aceh Besar and Peureulak,but the types of tombstones being adopted are not as many as at Samudera Pasai. The changes that occur are the addition of several parts gradually until like present form. Some types of tombstones developed ranging from decorative patterns up to size progress. But, some types of tombstones in recent times never appeared again. Tombstones, which called the "Aceh Stone" by Daniel Perret, is the result of a metamorphosis tombstones of Samudera Pasai.AbstrakNisan di Aceh mengalami perubahan bentuk (metamorfosis) dari yang sederhana hingga mencapai bentuknya seperti yang diketahui sekarang ini. Perubahan tersebut diawali dari beberapa nisan sederhana yang dapat ditemui di Samudera Pasai, tempat, awal mula penyebaran Islam di nusantara hingga mencapai puncaknya pada masa kesultanan Aceh Darussalam. Samudera Pasai hingga saat ini diyakini merupakan kerajaan Islam pertama di nusantara, yang menjadikannya sebagai tempat mengadopsi bentuk-bentuk nisan dari periode sebelumnya, yaitu masa Hindu Buddha. Tempat lain yang diyakini sebagai daerah terawal Islam di Nusantara adalah Lamreh/Lamuri di Aceh Besar, Peureulak, namun tipologi nisan yang diadopsi tidak sebanyak yang terdapat di Samudera Pasai. Perubahan yang terjadi adalah penambahan beberapa bagian secara bertahap hingga menjadi seperti bentuknya yang sekarang ini. Beberapa tipe nisan dikembangkan mulai dari pola hias hingga pengembangan pada ukurannya. Namun beberapa tipe nisan pada masa belakangan tidak pernah muncul lagi. Nisan yang pada akhirnya disebut “Batu Aceh” oleh Daniel Perret, adalah merupakan merupakan hasil dari metamorfose nisan-nisan dari Samudera Pasai.